Divorce of International Mixed Marriage and Marriage held Abroad and Indonesian Private International Law - Allagan, Tiurma M. Pitta (UI Scholars Hub, 2026)
The unstoppable tide of globalism not only brings an increasing commercial interconnectivity between nations, but also bonds of matrimony, and in turn, the chance of divorce. Indonesian courts entertaining international divorce cases is certainly not a rarity, neither divorce of the international mixed marriage nor the marriage that was held abroad. With two recent divorce cases having a foreign element, Indonesian courts declared having no jurisdiction under grounds of “litis pendentie” and forum non-convenience, including one by the Indonesian Supreme Court. In three other cases, the courts, after addressing the preliminary question of marriage, applied the “lex fori”, or Indonesian marriage law, as the applicable law to decide grounds of divorce. This article will thus examine five cases based on the principles of Indonesian private international law; firstly, on how Indonesian courts state that it has an authority to settle the submitted claims; and secondly, settling the case according to its law, as in line with the principle of “lex fori”. This research employs normative juridical research upon five cases of divorce that was settled before the Indonesian courts. This article finds that Indonesian judges imply international civil procedural law and Indonesian law as the applicable law in settling the divorce cases in question accordingly.